Electronic Properties of Defective MoS2 Monolayers Subject to Mechanical Deformations: A First‐Principles Approach - Bahmani, Mohammad; Faghihnasiri, Mahdi; Lorke, Michael; Kuc, Agnieszka-Beata; Frauenheim, Thomas (physica status solidi (b), 2020)
Monolayers (MLs) of group‐6 transition‐metal dichalcogenides (TMDs) are semiconducting 2D materials with direct bandgap, showing promising applications in various fields of science and technology, such as nanoelectronics and optoelectronics. These MLs can undergo strong elastic deformations, up to about 10%, without any bond breaking. Moreover, the electronic structure and transport properties, which define the performance of these TMD MLs in nanoelectronic devices, can be strongly affected by the presence of point defects, which are often present in the synthetic samples. Thus, it is important to understand both effects on the electronic properties of such MLs. Herein, the electronic structure and energetic properties of defective MoS2 MLs are investigated as subject to various strains, using density functional theory simulations. The results indicate that strain leads to strong modifications of the defect levels inside the bandgap and their orbital characteristics. Strain also splits the degenerate defect levels up to an amount of 450 meV, proposing novel applications. Applying first‐principles calculations, the influence of four different strains on the properties of the MoS2 defective monolayers (MLs) is studied. Formation energies are strongly tuned via strain. Breaking the symmetry of such MLs leads to degeneracy splitting of the defect levels, ranging from a few meV to more than 400 meV, depending on the point vacancy and type of strain.